Understanding the Effect of Impeller Configurations on Pullulan Production by Aureobasidium Pullulans RBF 4A3 - Kumar, Bhupender; Katoch, Anjula; Prasad, Gandham S.; Roy Choudhury, Anirban (Frontiers in Bioengineering and Biotechnology, 2019)
Mass transfer is one of the most important factors involved in viscous fermentation processes, like production of pullulan. Impellers play a crucial role in maintaining homogeneity and better mass transfer conditions during the fermentation process. The present study attempted to evaluate the efficiency of impellers with diverse configurations during pullulan fermentation. Initially, the mass transfer coefficients of 10 selected impellers were evaluated in an aqueous system. Among these, three impellers, namely, single helical ribbon, Rushton turbine, and Smith turbine impellers, were found to be more efficient and were further employed in the pullulan fermentation process. The results suggested that the single helical ribbon impeller was able to provide 24% higher pullulan production as compared to the Rushton turbine and Smith turbine impellers. The single helical ribbon was able to maintain the critical demand of dissolved oxygen in fermentation broth. Therefore, it may be commented that the single helical ribbon impeller configuration is suitable for higher production of pullulan during the fermentation process.